'Pillow technique' to improve lip support in the context of zygoma implant rehabilitation. Issue 6 (June 2023) - Hernández-Alfaro, F.; Ragucci, G.-M.-M.; Giralt-Hernando, M.; Caramês, J.; Valls-Ontañón, A.
Abstract: This study proposes a simple, off-the-shelf ancillary method for application in the dental rehabilitation of severe maxillary atrophy with zygoma implants, allowing simultaneous improvement of lip support in cases with a moderate lack of premaxillary projection. Three consecutive patients with an atrophic maxilla were evaluated retrospectively. All were treated with a fixed rehabilitation over four zygomatic implants and the pillow technique. The study variables included radiological assessment of the premaxilla volume, upper lip and perinasal soft tissue changes, clinical complications, and subjective evaluation of functional and aesthetic patient satisfaction based on a visual analogue scale. All of the zygomatic implants showed osseointegration. The survival rate was 100%. The immediate postoperative course was uneventful, and no surgical complications were noted at the follow-up visits. Radiological assessment of the premaxilla volume enhancement showed a final mean skeletal projection improvement of +9.4 mm, while the nasolabial angle decreased an average of + 0.6 mm. On the other hand, only small changes in nasal width were detected. Patient satisfaction with the functional and aesthetic outcomes at the 1-year follow-up was excellent. The pillow graft is an easy-to-handle technique that can be included in the armamentarium for moderately incrementing the maxillary sagittal dimension and enhancing lip support in the context of zygoma implant rehabilitation.